(untitled) (The Agriculturists, 2016)
The experiment was conducted to study the production and nutritional values of high yielding fodders by the goat farmers in Kobirhat and Subornochar upazilas of Noakhali District. The yields of high yielding forages had significant differences among the species. The average higher biomass were obtained from Napierhybrid (34), Napier-aerosa (20), Napierbazra (17.33) and Splendida (19). The Andropogon and Signal fodder had similar yields of 12.67 & 13.67 t/ha/cut. There was a significant (P<0.05) variations in the DM contents among the forages. The DM content (%) of Napier varieties ranged from 19.60 to 22.30, and highest value was found in Ruzi (27.90). A non-significant (P<0.05) differences were observed in the CP content (%) among the Napier and Splendida varieties. There was no significant difference in metabolizable energy content (MJ/kgDM) among the forages. The cultivation of high yielding fodders e.g. Napier hybrid, Napier aerosa, Napier bazra and Splendida may be practiced in the saline areas of Noakhali for high productivity of ruminants. The Agriculturists 2015; 13(1) 1-8